Corp-oralities - Munevar M., Dora Ines; Diaz C., Nohra Stella (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2009)
The goal of this paper is to share processes of corp-oral experimentation lived collectively. We want to expose the general process and the ways as the body appears, maintains and surpass the cognitive limits. The experience could be read as personal narrations but the interrelations between actions, feelings and experimentations invited us to think (us) as embodied subjectivities.